Report of a Working Group on Oat: Held in Menemen, Turkey, 25-27 Sept. 1984 - International Board for Plant Genetic Resources; United Nations Development Programme (1984)
Report of the ECPGR Oat Working Group meeting, 25-27 September 1984, Menemen, Turkey